The Effect of Pop Up Book Media on Increasing Dental Health Knowledge in Elementary School Children - Re, Pudentiana Rr; T, Siti Nurbayani; Atmasumarta, Tugiman; Lestari, Tri Riana; Purnama, Tedi (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Children are a very large group of people and have a high prevalence of dental caries. This is related to the correct tooth brushing behavior data which is 2.8% every day. Dental health promotion is an effort to increase children's knowledge whose success cannot be separated from the method of education and the role of the media. Pop-up book is one of the three-dimensional visual media that can be an alternative as a learning medium. Objective: This study aims to analyze the effect of pop up book media on increasing dental health knowledge of elementary school children. Methods: Pre-experimental research with pretest-posttest control group design. The sampling technique was purposive sampling as many as 64 children, consisting of 32 children in the intervention group and 32 children in the control group. The study was conducted at SDN 03 Cilandak Timur, South Jakarta from September to October 2021. The variable influence on the intervention group was pop up book media and the control group was flipchart media while the affected variable was dental health knowledge. The research instrument used a questionnaire about dental health. Data analysis used the SPSS program with the Paired Sample Test to compare the knowledge scores before and after the intervention and the independent t-test to compare the difference in knowledge scores between the intervention group and the control group. Results: The results of the Paired Sample Test on knowledge in the intervention group obtained p = 0.000 and in the control group was p = 0.182. The results of the independent t-test were obtained p = 0.000. Conclusion: Pop up book media is effective in increasing the dental health knowledge of elementary school children.